The Effects Of Virgin And Recycled PA12 Powders In SLS Processes On Occupational Exposures - Muhamad Damanhuri, Amir Abdullah; Mustafa, Mohd Syafiq Syazwan; Hariri, Azian; Ab Ghani, Sharin; Herawan, Safarudin Ghazali; Paiman, Nuur Azreeb (International Journal of Environmental Science and Development, 2021)
Particulate matter and ultrafine particles are emitted during the pre-processing and post-processing activities of selective laser sintering (SLS) processes, which is major concern to operators exposed to the powders. This study aims to determine the occupational exposure (in terms of the total particle concentration and respirable particulate concentration) during the pre-processing and post-processing activities of SLS processes using virgin and recycled polyamide 12 (PA12) powders. Personal air sampling was performed for each activity according to the NIOSH 0500 and NIOSH 0600 methods. Based on the results, both powders were uniform spheres with a particle size of 40–60 µm. The total particulate concentration was most significant during the following pre-processing activities: 1) pouring powder into the mixing machine and 2) transferring the powder to the SLS AM machine. The total particulate concentration and respirable particulate concentration were slightly higher for the virgin powder for these activities. In conclusion, the virgin and recycled PA12 powders were both inhalable and respirable, which poses serious health hazards to the SLS AM operators. Hence, it is essential for operators to use suitable personal protective equipment (including respirators) and the working practices need to be improved by automating some activities prevent manual powder handling.